Enhancing Quality of Life: Murottal Spiritual Care for Reducing Anxiety and Depression in Coronary Heart Disease Patients - A Holistic Systematic Review - Wisuda, Aris Citra; Sansuwito, Tukimin bin; Suraya, Citra (Yayasan Rumah Ilmu Professor, 2024)
Coronary heart disease is a chronic condition that can induce physiological and psychological changes in patients. One of the potential impacts is anxiety and depression related to the disease's progression. Patients undergoing procedures such as heart bypass often experience anxiety and depression due to various factors, particularly fear and a declining physical condition. Therefore, patients require therapy to alleviate anxiety and depression, promoting positive perceptions and relaxation to enhance their quality of life. Murottal therapy involves listening to the recitation of holy verses from the Quran, providing comfort and calmness to the patient. This research aims to assess the effectiveness of murotal therapy with Ar Rahman in addressing anxiety and depression in patients with coronary heart disease. The research methodology employed is a Literature Review, encompassing International Journals and National Journals published from 2018 to 2023. Literature was collected using Google Scholar and Pubmed databases with the keywords: Coronary Heart Disease, Anxiety, Depression, Murottal Ar-Rahman Therapy. The search yielded 317 articles based on the specified keywords. After filtering through predefined inclusion and exclusion criteria, 7 articles, comprising 6 National Journals and 1 International Journals, were reviewed. The results indicate that Ar Rahman murottal therapy can effectively reduce levels of anxiety and depression in patients with Coronary Heart Disease.